VIRTUAL REALITY-BASED LEARNING APPLICATION FOR SENSOR PROGRAMMING PRACTICUM MODULE - Fauzi, Amir Hasanudin; Prawita, Fat’hah Noor; Akhmadi, Akhmadi (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research aims to develop a learning application utilizing Virtual Reality (VR) technology for a sensor programming practicum module. By applying VR, it is expected to enhance students' conceptual understanding and practical skills in sensor programming more interactively and immersively. The application is designed to provide a virtual practicum environment where students can perform sensor programming experiments and practice without spatial and temporal limitations. The evaluation involves students and lecturers as users to measure the application's effectiveness in improving conceptual understanding and practical skills. The research results are expected to deliver an effective VR-based learning application that enhances students' conceptual understanding and practical skills in sensor programming. Additionally, it is expected that this application will receive positive feedback from users, indicating high satisfaction with the immersive learning experience offered.